Proceedings of the Mathematics, Informatics, Science, and Education International Conference (MISEIC 2018) 2018
DOI: 10.2991/miseic-18.2018.40
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Studentsr Mathematical Literacy Based on Mathematical Ability

Abstract: One of the 21st century skills is the mathematical literacy ability. The aim of this research was to describe the mathematical literacy ability student based on mathematical ability. This was qualitative descriptive research. The subjects of this research were three 8th grade students an Islamic secondary school at Yogyakarta. The data collection was by test and interview methods. The research instruments was mathematical literacy test used 4 PISA questions and semi-structured interview guidelines. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…Based on the previous explanation, the following is a summary of the numeracy of eighth grade students in solving AKM-like problems in the subdomain of equations and inequalities based on high, moderate, and low mathematical ability . These results are consistent with previous research that student with high mathematical ability could understand the objectives of the questions and formulate the problems contained in the questions as well as solve problems, interpreted results, and communicated the results of their interpretation well, while student with low mathematical ability couldn't use formulas, apply procedures, and provide proper reasons for the results obtained (Nurutami et al, 2018). In research conducted by Baharuddin et al (2021) with research results showing that student with high mathematical ability used various kinds of numbers and symbols related to basic mathematics to solve problems in various contexts of everyday life, analyzed the information displayed, and interpreted the results of the analysis to predict and make decisions.…”
Section: Pss -03 : What Conclusion Can You Draw? Ss-03 : So That Stat...supporting
confidence: 91%
See 1 more Smart Citation
“…Based on the previous explanation, the following is a summary of the numeracy of eighth grade students in solving AKM-like problems in the subdomain of equations and inequalities based on high, moderate, and low mathematical ability . These results are consistent with previous research that student with high mathematical ability could understand the objectives of the questions and formulate the problems contained in the questions as well as solve problems, interpreted results, and communicated the results of their interpretation well, while student with low mathematical ability couldn't use formulas, apply procedures, and provide proper reasons for the results obtained (Nurutami et al, 2018). In research conducted by Baharuddin et al (2021) with research results showing that student with high mathematical ability used various kinds of numbers and symbols related to basic mathematics to solve problems in various contexts of everyday life, analyzed the information displayed, and interpreted the results of the analysis to predict and make decisions.…”
Section: Pss -03 : What Conclusion Can You Draw? Ss-03 : So That Stat...supporting
confidence: 91%
“…Regarding numeracy, research by Nurutami, et al (2018) found that students with high mathematical ability understand the objectives of the questions and formulate the problems contained in the questions as well as solve; interpret problems; and present their answers fairly well. Meanwhile, students with low mathematical ability cannot use formulas; apply procedures; and give proper reasons for the results obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, students in the moderate mathematical ability group (S2) are at level 3 of mathematical literacy ability. Meanwhile, students in the high mathematical ability group (S3) are at level 4 of mathematical literacy ability, which means that they are still at the intermediate level; 3) Research conducted on 8th grade students at one of the Integrated Islamic Junior High Schools in Yogyakarta (Nurutami et al, 2018) showed the results that students with high math skills could achieve PISA math literacy level 2 and level 4, students with average math skills could achieve PISA math literacy level 2 , and students with low math skills cannot achieve mathematical literacy level 2, 3 or level 4 PISA; 4) Research conducted on 8th grade students at SMP N 3 Tarakan, North Kalimantan (Rahayu, 2022) showed that the mathematical literacy skills of class VIII students in solving hots questions were at level 4, namely: effectively work with models in concrete but complex situations limited in making assumptions, selecting and combining different representations, relating to real situations, using limited skills with few clear contextual views; 5) Research conducted on 8th grade students at Sultan Agung 4 Islamic Junior High School Semarang, Central Java (Ovan et al, 2018) showed that students with low metacognition had poor mathematical literacy skills, students with moderate metacognition had quite good mathematical literacy skills, and students with high metacognition had literacy skills math is very good; 6) Research on 8th graders at SMP Negeri 1 Tulis (Dessy Eka Jayanti, St. Budi Waluya, 2014) showed that the maximum students' mathematical literacy ability was at level 4, the mathematical literacy test was focused on real-life problems, outside of situations or problems that are often discussed in class during the mathematics learning process; 7) The research was conducted on 9th grade students at SMP Islam Al Azhar 27 Cilegon (Muslimah & Pujiastuti, 2020), which showed that students in the low mathematical ability group (S1) were at level 2 of mathematical literacy ability. Furthermore, students in the moderate mathematical ability group (S2) are at level 3 of mathematical literacy ability.…”
Section: Number Of Studimentioning
confidence: 99%
“…Dalam PISA kemampuan literasi matematis didefinisikan sebagai kemampuan seseorang untuk merumuskan, menggunakan, dan menafsirkan matematika dalam berbagai konteks. Hal ini meliputi penalaran matematika dan pengunaan konsep, prosedur, fakta dan alat matematika untuk mendeskripsikan, menjelaskan, dan memprediksi fenomena (Sari, 2015;Nurutami, 2018). Kemampuan literasi matematis membantu seseorang untuk memahami peran atau kegunaan matematika dalam kehidupan sehari-hari dan sekaligus menggunakannya untuk keputusan-keputusan yang tepat atas berbagai permasalahan (Makhmudah, 2018).…”
Section: Pendahuluanunclassified
“…Hal ini dapat dilihat dari hasil penelitian PISA, rata-rata skor internasional kemampuan literasi matematis yaitu 500 diposisi level 3, sedangkan rata-rata skor literasi matematis siswa Indonesia adalah 375 diposisi level 1, dan adapun level tertinggi yang mampu dicapai siswa Indonesia adalah level 3 {Formatting Citation}. Sejalan dengan hal tersebut, hasil survei PISA tahun 2018 ratarata skor literasi matematis siswa Indonesia masih berada dibawah rata-rata OECD (Organisation for Economic Co-operation and Development), yaitu sebesar 379 dengan posisi 73 dari 79 negara, dimana rata-rata OECD sebesar 489 (OECD, 2019;Nurutami, 2018). Hal tersebut menunjukkan bahwa ada perbedaan ketercapaian level kemampuan literasi matematis di Indonesia.…”
Section: Pendahuluanunclassified